Building Dynamic Capabilities for Enhanced Organisational Performance - Adnan Al Zoukani (2025)
This study investigates absorptive capacity in tourism organisations, focusing on their ability to gain and maintain a competitive edge through agility and value creation from external knowledge. The aim is to improve organisational performance and competitiveness amidst changing environments. The research examines how absorptive capacity affects strategic agility, value creation, and overall performance, emphasizing the importance of acquiring external knowledge for resilience and competitiveness. Past literature highlights strategic agility as a mediator between absorptive capacity and performance, and the role of value creation, especially in service value and customer satisfaction, in enhancing organisational outcomes. The study adopts a holistic view of organisational performance, integrating innovation and operational metrics through Dynamic Capability theory. Using a quantitative, deductive approach with 347 respondents from the UAE’s tourism sector, the research employs PLS-SEM and SmartPLS for analysis. Theoretical contributions include clarifying the significance of external knowledge absorption for tourism organisations and guiding managerial strategies for competitive advantage and market survival. Practical implications stress the need for effective employee training and development to ensure customer satisfaction and organisational resilience.